2020
DOI: 10.1016/j.wroa.2019.100040
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bacterial and viral indicator organisms in full-scale aerobic granular sludge and conventional activated sludge systems

Abstract: The aim of this study was to evaluate the effectiveness of the novel aerobic granular sludge (AGS) wastewater treatment technology in removing faecal indicator organisms (FIOs) compared to the conventional activated sludge (CAS) treatment system. The work was carried out at two full-scale wastewater treatment plants (WWTP) in the Netherlands, Vroomshoop and Garmerwolde. Both treatment plants have a CAS and AGS system operated in parallel. The parallel treatment lines are provided with the same influent wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…coli reactor was within the range previously reported for E. coli in full-scale AGS systems. However, the MS2 bacteriophage removal (0.7 Log10) was lower than reported [98]. It is worth mentioning that full-scale AGS systems contain both a large granular sludge fraction and a smaller flocculent sludge fraction [75].…”
Section: Fate Of the Target Surrogates During The Operational Conditi...mentioning
confidence: 66%
See 1 more Smart Citation
“…coli reactor was within the range previously reported for E. coli in full-scale AGS systems. However, the MS2 bacteriophage removal (0.7 Log10) was lower than reported [98]. It is worth mentioning that full-scale AGS systems contain both a large granular sludge fraction and a smaller flocculent sludge fraction [75].…”
Section: Fate Of the Target Surrogates During The Operational Conditi...mentioning
confidence: 66%
“…Besides a good treatment performance concerning the water quality parameters, two recent studies showed the capability of the AGS technology in removing bacterial and viral indicator organisms from sewage. Barrios-Hernández, Pronk [98] and Thwaites, Short [85] compared removal efficiencies in AGS and CAS full-and pilot-scale WWTP. The AGS full-scale systems can just as effectively remove indicator organisms as the CAS process.…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that WWTP do provide a suitable environment for the proliferation of ARBs containing a high proportion of resistant bacteria. Berrios-Hernandez [ 113 ] inferred that the removal of fecal indicator organisms is not correlated to water quality parameters but is generally dependent upon the treatment technology used. In the case of E. coli , total suspended solids have been positively correlated with its removal, supporting the efficacy of primary and secondary treatment units for the removal of the microbial population.…”
Section: Review Findingsmentioning
confidence: 99%
“…Alternatively, viral removal can be promoted by physical procedures, mainly by biomass adsorption, because viruses are adhered to the surface and subsequently microbial inactivation occurs [33]. Despite efforts to increase knowledge about the removal of pathogens, few studies have concluded that AGS is able to remove F-specific RNA bacteriophages such as E. coli, Enterococci and thermotolerant coliforms as efficiently as CAS [34]. However, there is a clear need for further studies to determine if the removal mechanisms in the two systems are comparable.…”
Section: Advantages Over Conventional Activated Sludgementioning
confidence: 99%